The distinctly competent district councillor - Jonasson, Jonas, 1961- (4th Estate, 2026)
"All over the world, people sleep blissfully in Traumbett beds. These marvellous feats of German engineering have successfully cornered the mattress market everywhere. Everywhere, except Sweden and owner Konrad Kaltenbacher Jr is desperate to expand there. With Konrad Jr's sights set firmly on stylish Stockholm, Julia Bäck, district councillor of the small, decaying town of Halstaholm, has plans of her own. Seeing an opportunity to attract 800 new jobs, Julia jumps into spearheading a persuasive campaign to win the contract. A roundabout is hastily renamed in honour of Angela Merkel; a German school is quickly established under the leadership of a ten-year-old boy and three elderly pensioners; and the town swimming pool is rapidly transformed into a beerhouse - it had been empty for years anyway! Julia's get-up-and-go impresses the German boss ... but has she made herself a tricky bed to lie in?"--